On Situation Control Problem Settings with Multiple Stakeholders Using Cognitive Maps - Avdeeva, Z. K.; Kovriga, S. V. (Automation and remote control, 2020)
We propose control problem settings for a situation with multiple active subjects and a general scheme of their solution using cognitive maps. We identify some promising areas of application where these problems can be needed and areas for further research.